The comparison of prognostic value of VEGF and MMP-9 in non-small cell lung cancer during three-year observation after anti-tumour treatment - Kopczyńska, Ewa; Dancewicz, Maciej; Kowalewski, Janusz; Tyrakowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2008)
Background: There are over 150 prognostic factors in lung cancer. Among these factors three groups of factors are distinguished: essential, additional, and new or promising. This last group includes: serum tumour markers, markers of cellular proliferation and adhesion, regulators of cellular growth and growth factors. Increased expression of vascular-endothelial growth factor is recognized to be an unfavourable prognostic factor in lung cancer. On the other hand, decidedly less is known about the prognostic value of metalloproteinase 9. Both factors, VEGF and MMP-9, play an important role in tumour angiogenesis, tumour growth, invasion and metastasis. Aim of the study: The aim of this study was to compare the value of increased concentration of VEGF and MMP-9 in estimation of survival time and relapse in non-small cell lung cancer during three-year observation after anti- -tumour treatment. Material and methods: The study group constituted patients with non-small cell lung cancer, in whom increased concentrations of VEGF (group A) and MMP-9 (group B) were found. Serum concentrations of VEGF and MMP-9 were evaluated by ELISA test. Results: The percentage of three-year: 1) overall survival in group A was 80%, in group B 82.6%, 2) disease-free survival in group A was 32.4%, in group B 30.9%, 3) locoregional recurrence-free survival in group A was 73.5%, in group B 68.2%, 4) metastasis-free survival in group A was 58.3%, in group B 57.7%. Median overall survival in both groups was identical and it was 31 months. Conclusions: The prognostic value of increased serum VEGF and MMP-9 concentration in non-small cell lung cancer patients is similar.